Childfree, Kebebasan Manusia, dan Alienasi dalam Novel Ours: Tinjauan Filsafat Eksistensialisme Jean-Paul Sartre: Penelitian - Deviana Rasyid; Herson Kadir; La Ode Gusman Nasiru (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research explored the representation of the childfree lifestyle in the novel Ours by Adrindia Ryandisza through the lens of Jean-Paul Sartre's existentialism The novel narrates the story of a protagonist who consciously chooses not to have children and illustrates how this decision impacts her relationships with her partner, family, and social environment. This research focused on two main issues: (1) the portrayal of childfree decisions in relation to the concept of human freedom, and (2) the perspective of alienation. It employed a descriptive qualitative method, with data collected through close reading and note-taking, followed by stages of identification, classification, analysis, description, and conclusion drawing. The results revealed that the decision to be childfree reflects individual freedom, emphasizing awareness, responsibility, and control over one's own life However, this freedom also leads to feelings of alienation rooted in societal norms and stigmatization. This research concluded that Ours offers a clear representation of how the childfree choice is an existential act of freedom that demands full responsibility, while also highlighting the challenges faced by individuals whose life choices deviate from social conventions.